2017
DOI: 10.7498/aps.66.054210
|View full text |Cite
|
Sign up to set email alerts
|

Parallel magneticcontrolled THz modulator based on two-dimensional magnetized plasma photonic crystal

Abstract: THz waves are very good candidates for high-capacity wireless links since they offer a much higher bandwidth than RF frequencies. Photonic crystal (PC) offers a new opportunity for integrated THz wave devices. It permits the integrated devices to be miniaturized to a scale comparable to the wavelength of the electromagnetic wave. Considering their governing properties such as photonic band gap (PBG) and photon localization effect to control electromagnetic wave propagations, PC-based THz modulator has attracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The luminescence intensity is directly proportional to the number of electrons in the Γ valley, which has been demonstrated in previous studies. [6,[11][12][13][14] To investigate the distributions of the electrons in the three valleys corresponding to different incident THz pulses, the Boltzmann equation is used to describe the motion of electrons in the THz field, which is studied by the ensemble Monte Carlo method [9,10,[15][16][17][18][19][20][21][22][23]…”
Section: Physical Mechanism and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The luminescence intensity is directly proportional to the number of electrons in the Γ valley, which has been demonstrated in previous studies. [6,[11][12][13][14] To investigate the distributions of the electrons in the three valleys corresponding to different incident THz pulses, the Boltzmann equation is used to describe the motion of electrons in the THz field, which is studied by the ensemble Monte Carlo method [9,10,[15][16][17][18][19][20][21][22][23]…”
Section: Physical Mechanism and Modelmentioning
confidence: 99%
“…In order to enhance the performance and functionalities of the detectors for various applications, a novel theoretical THz pulse detection method was proposed in a previous study. [6] The electron transport caused by a THz pulse has aroused significant interest, [6][7][8][9][10] which is the basis of the new de-tection theory. In our earlier work, it has already been suggested that the coherent detection of THz pulses can be realized based on the THzinduced time-resolved luminescence quenching, [6] because the changes in the luminescence and THz pulse waveforms are reversed when the THz pulse irradiates the semiconductor under a direct-current (DC) voltage at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…THz pulse based on its high-field transport and ultrafast characteristics has been applied to semiconductor modulation technology which has seen rapid development in recent years. [1][2][3][4][5][6][7][8][9][10][11][12] Especially, it is possible to study the nonlinear modulation of the carriers by THz pulse precision delay in semiconductors. For example, scholars have observed nonlinear ultrafast modulations of intense terahertz pulses in Ge, Si, GaAs, and InGaAs.…”
Section: Introductionmentioning
confidence: 99%